The Concept of Chain Lending (‘Ariyah) from the Perspectives of the Maliki and Shafi’i Schools of Thought - Raziq, Luthfi (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
AbstractThe tradition of lending and borrowing items has become common in society. However, this practice often creates problems when it develops into chain lending, namely when an item that has been borrowed is subsequently lent out to another party. In reality, many people neglect such situations' legal and social-ethical aspects, even though the item in question does not belong to them. In Islamic jurisprudence, scholars differ in their opinions regarding the permissibility of chain lending (‘Ariyah). This study aims, first, to explain the concept of chain lending (‘Ariyah) from the perspective of Islamic law; and second, to compare the views of the Maliki and Shafi'i schools regarding this matter. This research employs a qualitative method with a library research approach. Primary data are derived from classical fiqh texts of the Maliki and Shafi'i schools and other scholarly works relevant to the discussion of ‘Ariyah. Secondary data are obtained from supporting literature such as comparative fiqh books, journal articles, and previous studies discussing the practice of ‘Ariyah. The data analysis technique used is descriptive-analytical and comparative. The study concludes that the terminology ‘Ariyah' has two primary meanings. First, according to the Maliki and Hanafi schools, ‘Ariyah is regarded as a form of ownership of benefits, allowing the borrower to lend the item to another party without the owner's permission, provided that its usage remains the same. Second, the Shafi'i and Hanbali schools consider ‘Ariyah to only grant the right to use the item, not to transfer the lending right to another person, and therefore, the borrower is not authorized to lend it further. Keywords: Chain ‘Ariyah, Maliki School, Shafi’i School. AbstrakTradisi saling meminjamkan barang telah menjadi kebiasaan yang lumrah di masyarakat. Namun, praktik ini sering menimbulkan persoalan ketika berkembang menjadi pinjam-meminjam berantai, yaitu ketika barang yang dipinjamkan kembali dipinjamkan kepada pihak lain. Dalam kenyataannya, banyak orang mengabaikan aspek hukum maupun etika sosial dalam situasi ini, padahal barang tersebut bukan miliknya sendiri. Dalam kajian fikih, para ulama berbeda pendapat mengenai kebolehan praktik ‘Ariyah berantai. Penelitian ini bertujuan: Pertama, menjelaskan konsep ‘Ariyah berantai dalam perspektif hukum Islam; Kedua, membandingkan pandangan mazhab Maliki dan mazhab Syafi’i terkait hal tersebut. Penelitian ini menggunakan metode kualitatif dengan pendekatan kepustakaan. Data primer diperoleh dari kitab-kitab fikih klasik Mazhab Maliki dan Mazhab Syafi’i, serta karya ulama lain yang relevan dengan pembahasan ‘Ariyah. Sedangkan data sekunder berasal dari literatur pendukung seperti buku fikih perbandingan, artikel jurnal, maupun hasil penelitian terdahulu yang membahas praktik ‘Ariyah. Teknik analisis data dilakukan dengan metode deskriptif-analitis dan komparatif. Penelitian ini menghasilkan kesimpulan bahwa terminologi ‘Ariyah memiliki dua pemahaman utama, yaitu. Pertama, menurut mazhab Maliki dan Hanafi, ‘Ariyah dipandang sebagai bentuk kepemilikan manfaat, sehingga peminjam diperbolehkan meminjamkan barang tersebut kepada pihak lain tanpa izin pemilik, selama penggunaannya sama. Kedua, mazhab Syafi’i dan Hanbali menilai ‘Ariyah hanya memberi hak menggunakan barang, bukan mengalihkan hak pinjam kepada orang lain, sehingga peminjam tidak berwenang meminjamkannya lagi. Kata Kunci: ‘Ariyah berantai, Mazhab Maliki, Mazhab Syafi’i.